2023
DOI: 10.3390/polym16010001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shock-Variable Environmental Temperature and Humidity Conditions on 3D-Printed Polymers for Tensile Properties

Marcin Głowacki,
Katarzyna Skórczewska,
Krzysztof Lewandowski
et al.

Abstract: The article presents the research results on the influence of variable shock conditions, such as temperature and water, thus reflecting shock atmospheric conditions during freezing and thawing, on the properties of samples produced using 3D printing technology from commonly used materials such as ABS, HIPS, PLA, and ASA. Understanding how different environmental conditions affect the quality, reliability, and durability of 3D prints can help to optimize the printing process and provide valuable information abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The specimens were subjected to forces from the zero pulses, and the value of the amplitude stress, σ a , was related in percentage to the tensile strength, as described in Section 2.3 . At each load level, 3 specimens were tested in series [ 31 ]. Tests were conducted at a frequency of 2 Hz, and the number of load cycles to specimen failure was recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimens were subjected to forces from the zero pulses, and the value of the amplitude stress, σ a , was related in percentage to the tensile strength, as described in Section 2.3 . At each load level, 3 specimens were tested in series [ 31 ]. Tests were conducted at a frequency of 2 Hz, and the number of load cycles to specimen failure was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed assuming a significance level below 0.05. A similar method was used in our previous publication [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Afshar and Mihut [ 30 ] found that the durability of 3D-printed polymer composite parts could be improved by depositing a thin metallic copper film on the surface of the 3D-printed parts. Glowacki et al [ 31 ] studied the effect of freeze–thaw cycling on the durability of 3D-printed acrylonitrile butadiene styrene and polylactic acid and found that one cycle lasting seven days was enough to alter the mechanical properties of the materials.…”
Section: Introductionmentioning
confidence: 99%